Pendampingan Pengenalan Musuh Alami Hama Potensial Pada Tanaman Kentang Di Sembalun - Muhammad Sarjan; Ruth Stella P. Thei; Hery Haryanto; Mery Windarningsih (Pascasarjana Universitas Mataram, 2022)
Interventions in the use of technology to farmers as an alternative in Pest Management in potato cultivation are highly expected by farmers in the Sembalun area. Therefore, it is worth trying its utilization on potato crops to control important pests that attack. The method used in this activity is the Action Research Method by applying the Participatory Action Program approach from participants through discussions, and group work on all activities. The results of the group discussion showed that the group members had largely not recognized the types and functions of natural enemies in Potato Pest Management. After joint observations accompanied by the team, participants actually knew the types of natural enemies, both predators, and parasitoids, but they did not know the role of natural enemies in the agroecosystem. After finishing the meeting, the group realized the importance of maintaining the presence of natural enemies of pests in the potato agroecosystem so that the use of pesticides, which had been the main control technique for pests, could be reduced. Thus, it is hoped that the potato farming business in Sembalun will increase profits and produce environmentally friendly products